Role of Swarnaprashan in Children: A Systematic Review - Khan, Sahadat; Ojha, Nisha Kumari (International Research Journal of Ayurveda & Yoga, 2022)
Background: Swarnaprashan is a herbo-mineral Ayurveda preparation recommended in pediatric age group to enhance immunity and intellect since antiquity. Numbers of advocates are available for the practice of Swarnaprashan and its utility. Aim & Objective: The current review is aimed to assess the role of Swarnaprashan in children which could potentially have multifaceted benefits. Material and Method: A systematic review was conducted following PRISM ScR guidelines. Randomized Controlled Trials (RCTs) analyzing the role of Swarnaprashan in children and published articles between 2001 to 2022 year were included in this study. Electronic databases were screened viz. PubMed, Medline, Google Scholar, Scopus. The following keywords were used: “Swarnabinduprashan, Suvarnabinduprashan, Suvarnaprashan, and Swarnaprashana. To obtain additional data a manual search was performed using the reference lists of included articles. Results: Present systematic review reveals the beneficial health effects of Swarnaprashan: a) Immunomodulatory effect b) Effect on ITQOL c) Effect on hematological biochemical parameters/ Assessment of safety d) Effect on cognition e) Effect on growth, development and behavior. Conclusion: Present systematic review proves the role of Swarnaprashana in enhancing the cognition, physical growth, development as well as protection against the diseases by enhancing the immunity. There for Swarnaprashan could serve as drug of multimodal action at various levels which could lead complete development of a child.